Legal integration and language diversity - Baaij, C. J. W. (Oxford University Press, 2018)
The European pursuit for legal integration and language diversity poses a puzzling question: how can the EU create uniform laws in 24 official languages successfully? This work argues that the answer lies in elevating the English language version, and seeking literalism over fluency in allying the other language versions.
10.1093/oso/9780190680787.001.0001
Keywords: Rechtsetzung; Mehrsprachigkeit